Pengasuhan dan Stimulasi Tumbuh Kembang Anak Melalui Pelayanan Terintegrasi Taman Penitipan Anak dan Baby/Kids Spa Griya Sehat - Made Ermayani; Aprilia Nuryanti; Yovita Erin Sastriani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Difficulties about parenting for working parents and how to stimulate the growth of children's development are a challenge to the business. Parents who entrust children expect to be well cared for by care for health. Griya Sehat Bayi dan Balita is an effort that provides comprehensive services to the needs of parents to monitor and develop the growth and development of infants or toddlers. The specific target this program is to provide a vehicle for universities to develop the application of technology in the health and nursing of infants/toddlers based on the results of research and community service. The service provided is a child care center with online CCTV service, assessment, and stimulation of growth and development of SPA for a toddler. Griya Sehat Bayi dan Balita gives job opportunities for alumni and becomes a place of internship for the student of STIKES Dirgahayu Samarinda. The daycare unit opened in March with a capacity of 10 children with four sitter-in. SPA units operate from May 2018 with a therapist, an admin, and four volunteers. The parent's evaluation of daycare in the 80% is satisfied and 20% stated very satisfyingly. Greeting, friendliness, speed of response and completeness of the facility is considered very satisfactory. Clarity type of service, cleanliness, and comfort is considered satisfactory by the customer.